2017
DOI: 10.1021/jacs.6b10776
|View full text |Cite
|
Sign up to set email alerts
|

Substituted Polyesters by Thiol–Ene Modification: Rapid Diversification for Therapeutic Protein Stabilization

Abstract: Many proteins, especially those used as therapeutics, are unstable to storage and shipping temperatures, leading to increased costs in research and industry. Therefore, the design and synthesis of novel stabilizers is an important area of investigation. Herein we report new degradable polymers that stabilize proteins to environmental stressors such as refrigeration and elevated temperature. Specifically, polycaprolactones with different pendant groups were synthesized and surveyed for their ability to stabiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
127
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 83 publications
(127 citation statements)
references
References 79 publications
0
127
0
Order By: Relevance
“…[13] And our group has previously reported on glycopolymers with trehalose side chains for enhancing stability of a wide range of proteins against lyophilization, mechanical, and heat stress. [14][15][16][17] Yet, most of the reported stabilizers are not degradable.…”
Section: Doi: 101002/marc201700652mentioning
confidence: 99%
See 3 more Smart Citations
“…[13] And our group has previously reported on glycopolymers with trehalose side chains for enhancing stability of a wide range of proteins against lyophilization, mechanical, and heat stress. [14][15][16][17] Yet, most of the reported stabilizers are not degradable.…”
Section: Doi: 101002/marc201700652mentioning
confidence: 99%
“…[18,19] To address this need, we recently described stabilizing polymers with polyester backbones. [17] Specifically, polycaprolactone was prepared with zwitterionic and trehalose side chains. These polymers were highly effective protein stabilizers and also degraded through ester hydrolysis.…”
Section: Doi: 101002/marc201700652mentioning
confidence: 99%
See 2 more Smart Citations
“…[28] Other types of polymers,i ncluding biodegradable poly(amino acid)s and nonbiodegradable poly(glycerol), poly(2-oxazoline), poly(acrylamide), poly(vinylpyrrolidone),a nd poly(N-(2-hydroxypropyl)methacrylamide), have also been proposed as PEG alternatives,however their immunogenicity when conjugated to proteins has not been fully studied. [30] The PCL zwitterion was shown to preserve therapeutic protein activities.However,the hydrophobicity of the long caprolactone repeating unit and low zwitterion density might compromise its hydration capacity and its stealth properties. It would be interesting to develop ab iodegradable zwitterionic polymer.M aynard et al reported the development of ab iodegradable zwitterionic polyester by attaching carboxybetaine moieties to an allyl-substituted polycaprolactone (PCL) through thiol-ene chemistry.…”
mentioning
confidence: 99%